MENIMBANG EFEKTIVITAS ASURANSI SEBAGAI INSTRUMEN PERLINDUNGAN FINANSIAL “APAKAH RISIKO DAN MANFAAT SEIMBANG?” - Mairani Adelia; Arsyadona Arsyadona; Aura Tafana; Sayyida Marwah; Bayu Andika (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
This article discusses the role of insurance as a financial risk protection tool and evaluates the gap between the promise of protection offered and the reality experienced by customers. The study is based on key theories in insurance, including risk theory, premiums, claims, and time value of money, to explain how insurance works as a risk management mechanism. Data from books, journals, academic articles, and insurance industry reports are critically analyzed through a qualitative approach with a library research method. The results of the analysis show that there is a gap between the promise of insurance protection and the reality faced by customers, especially related to the low insurance literacy in the community and also provide a holistic view of the role and challenges of insurance as a risk mitigation instrument in the modern socio-economic context. This study aims to analyze the effectiveness of insurance protection in managing unexpected financial risks, focusing on the theory of risk, premiums, claims, and time value of money. The study also considers people's insurance literacy, the potential of digitalization, and the need for stronger regulations to address issues of limited access and transparency of insurance in Indonesia. In conclusion, while insurance is important for risk mitigation, stronger regulations and better literacy are needed to ensure fairer and more effective protection.